Quantification of betel quid hygroscopicity in context to saliva: A proof of concept for future studies - Sachin C. Sarode; Nilesh Kumar Sharma; Gargi Sarode; Devyani Bhatkar; Nistha Ananda (Journal of Oral Biology and Craniofacial Research)
The physical and chemical properties of various constitutional ingredients of betel quid (BQ) are well known in the literature. However, BQ as a whole has been rarely investigated for identifying its physical properties that can impact and modulate the disease progression of various pathologies, mainly oral submucous fibrosis (OSMF). It is quite conceivable that in the oral cavity environment, the amalgamated BQ might absorb saliva by virtue of its hygroscopic properties. As a proof of concept, we developed a methodology to quantify the hygroscopicity of the ‘whole BQ’ when it is mixed with saliva. To the best of our knowledge, this is the first study to report and quantify the hygroscopicity of BQ when mixed with saliva, and this forms a proof of concept for future implications in the pathogenesis of various pathologies.